GSH-responsive polymeric micelles-based augmented photoimmunotherapy synergized with PD-1 blockade for eliciting robust antitumor immunity against colon tumor - Chenlu Huang; Xinyu Yang; Huidong Li; Li Zhang; Qing Guo; Qingyu Yu; Hai Wang; Linhua Zhang; Dunwan Zhu (Journal of Nanobiotechnology)
Abstract Phototherapy is a promising antitumor modality, which consists of photothermal therapy (PTT) and photodynamic therapy (PDT). However, the efficacy of phototherapy is dramatically hampered by local hypoxia in tumors, overexpression of indoleamine 2,3-dioxygenase (IDO) and programmed cell death ligand-1 (PD-L1) on tumor cells. To address these issues, self-assembled multifunctional polymeric micelles (RIMNA) were developed to co-deliver photosensitizer indocyanine green (ICG), oxygenator MnO2, IDO inhibitor NLG919, and toll-like receptor 4 agonist monophosphoryl lipid A (MPLA). It is worth noting that RIMNA polymeric micelles had good stability, uniform morphology, superior biocompatibility, and intensified PTT/PDT effect. What’s more, RIMNA-mediated IDO inhibition combined with programmed death receptor-1 (PD-1)/PD-L1 blockade considerably improved immunosuppression and promoted immune activation. RIMNA-based photoimmunotherapy synergized with PD-1 antibody could remarkably inhibit primary tumor proliferation, as well as stimulate the immunity to greatly suppress lung metastasis and distant tumor growth. This study offers an efficient method to reinforce the efficacy of phototherapy and alleviate immunosuppression, thereby bringing clinical benefits to cancer treatment. Graphical Abstract